Jordan : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2012)
This Selected Issues Paper focuses on economic condition, energy subsidies, and oil prices in Jordan. Energy price subsidies pose a serious fiscal risk in the present context of increasing and volatile international prices. The macroeconomic situation in Jordan is closely tied to that of other countries in the Middle East. From a policy perspective, macroeconomic and structural policies in Jordan should be conducted in such a way that the vulnerability of the country to sudden stops or reversals of external income flows is reduced.